وقف النقود يف التاريخ اإلسالمي: دراسة استكشافية - Musa, Mohamed Kabir; Hasan, Aznan; Zakariyah, Habeebullah (Brabdo for Educational Services, 2022)
تهدف هذه الد ا رسة إلى استكشاف م ا رحل التاريخية التي مر عليها وقف النقود في التاريخ الإسلامي. فجاءت هذه الد ا رسة للإجابة عن الأسئلة الآتية: ما هو وقف النقود، وما الم ا رحل التي مر عليها في التاريخ الإسلامي، وما تطبيقاته المعاصرة؟ وقد اعتمد البحث على المنهج الاستق ا رئي الذي من خلاله تم تتبع المعلومات من المصادر التاريخية والفقهية قديمًا وحديثًا، كما تبنى البحث المنهج الوصفي التحليلي لتحليل المفاهيم الأساسية المتعلقة بالد ا رسة بشكل نظري، وخلصت الد ا رسة إلى مجموعة من النتائج أهمها: أن العلماء تناولوا الوقف النقدي من خلال قرن الثاني إلى ال ا ربع عشر الهجريين؛ إلا أنه لم يتم تطبيقه في تلك الوقت؛ لكن تم تطبيقه في عصر الخلافة العثمانية، ونظ اً ر للدور الذي يلعبه الوقف النقدي في جميع نواحي الحياة؛ الاقتصادية، والاجتماعية والتربوية تم تطبيقه بأشكال مختلفة في البلدان الإسلامية والأقليات المسلمة في هذا العصر. This study aims to explore the historical stages of the cash waqf in Islamic history. This study came to answer the following questions: What is cash waqf, what stages cash waqf has gone through Islamic history, and what are the contemporary application of cash waqf? The research relied on the inductive approach through which information was collected from historical and jurisprudential sources, classical and modern. The research also adopted the descriptive analytical approach to analyze the essential concepts of the research theoretically related to the study. The study detected that those scholars during the second to the fourteenth centuries of the Hijra had discussed issues related to cash waqf. However, it was not implemented at that time; but it was applied in the era of the Ottoman Caliphate. And due to the roles, that cash waqf plays in all aspects of life; Economic, social, and educational it has been applied in various forms in Islamic countries and Muslim minorities in this era.